Innovative approaches for treatment of osteosarcoma. Issue 4 (February 2022) - Rothzerg, Emel; Pfaff, Abigail L; Koks, Sulev
Osteosarcoma (OS) is the most common primary malignant bone tumor, which usually occurs in children and adolescents. It is generally a high-grade malignancy presenting with extreme metastases to the lungs or other bones. The etiology of the disease is multifaceted and still remains obscure. A combination of surgery and chemotherapy has played a major role in the treatment of OS over the past three decades, and consequently, the overall survival rates for the disease have remained unchanged. Therefore, there is an urgent need to employ new comprehensive analyses and technologies to develop significantly more informative classification systems, with the aim of developing more effective and less toxic therapies for OS patients. This review discusses the existing knowledge of OS therapy and potential methods to develop novel therapeutic agents for the disease.